SAT0035 Ankylosing spondylitis, psoriatic arthritis and reactive arthritis show increased bone resorption and differ with regard to bone formation. (1st June 2001) - Grisar, J; Aringer, M; Redlich, K; Bernecker, PM; Wolozcszuk, W; Smolen, JS; Pietschmann, P
Abstract : Background: It is well established that rheumatoid arthritis is associated with severe alterations of bone metabolism. In seronegative spondylarthropathies (SSPs), however, data on bone turnover are scarce and conflicting. Objectives: Methods: We studied biochemical markers of bone resorption (urinary deoxy-pyridinoline (D-Pyr) and cross-linked telopeptide of collagen-1 (ICTP)), bone formation markers (osteocalcin (OC) and bone specific isoenzyme of alkaline phosphatase (BAP)) as well as serum levels of osteoprotegerin (OPG, a glycoprotein which prevents the differentiation and activation of osteoclasts) in 30 patients with ankylosing spondylitis (AS), 23 patients with psoriatic arthritis (PsoA), 10 patients with reactive arthritis (ReA) and sex- and age matched healthy controls (HC). Results: Markers of bone resorption were significantly increased in AS, PsoA and ReA patients (Table 1 ). In contrast, bone formation markers were found to be heterogeneous: OC was increased in AS, but not in PsoA or ReA and the levels of BAP were elevated only in patients suffering from PsoA (Table 1 ). Serum levels of OPG were significantly increased in the AS and PsoA-group (Table 1 ). Furthermore, dual energy x-ray absorptiometry (DXA) measurements of the lumbar spine and the femoral neck, performed in a subgroup of patients, showed clearly decreased T-scores (lumbar spine -0.99 ± 1.33, femoral neck -1.95 ± 1.33) in patients suffering from AS. In PsoA bone mineral density was within the normal range. * = p < 0.05. ** = p < 0.001. Conclusion: Our results suggest significant alterations of bone metabolism in patients with SSPs. It is tempting to speculate that the increased OPG levels in AS and PsoA may represent a compensatory mechanism following enhanced bone resorption.